The protective effect of cilostazol on isolated rabbit femoral arteries under conditions of ischemia and reperfusion: the role of the nitric oxide pathway (Clinics, 2012)
OBJECTIVES: The clinical significance of ischemia/reperfusion of the lower extremities demands further investigation to enable the development of more effective therapeutic alternatives. This study investigated the changes in the vascular reactivity of the rabbit femoral artery and nitric oxide metabolites under partial ischemia/ reperfusion conditions following cilostazol administration. METHODS: Ischemia was induced using infrarenal aortic clamping. The animals were randomly divided into seven groups: Control 90 minutes, Ischemia/Reperfusion 90/60 minutes, Control 120 minutes, Ischemia/Reperfusion 120/90 minutes, Cilostazol, Cilostazol before Ischemia/Reperfusion 120/90 minutes, and Ischemia 120 minutes/Cilostazol/ Reperfusion 90 minutes. Dose-response curves for sodium nitroprusside, acetylcholine, and the calcium ionophore A23187 were obtained in isolated femoral arteries. The levels of nitrites and nitrates in the plasma and skeletal muscle were determined using chemiluminescence. RESULTS: Acetylcholine-and A23187-induced relaxation was reduced in the Ischemia/Reperfusion 120/90 group, and treatment with cilostazol partially prevented this ischemia/reperfusion-induced endothelium impairment. Only cilostazol treatment increased plasma levels of nitrites and nitrates. An elevation in the levels of nitrites and nitrates was observed in muscle tissues in the Ischemia/Reperfusion 120/90, Cilostazol/Ischemia/Reperfusion, and Ischemia/ Cilostazol/Reperfusion groups. CONCLUSION: Hind limb ischemia/reperfusion yielded an impaired endothelium-dependent relaxation of the femoral artery. Furthermore, cilostazol administration prior to ischemia exerted a protective effect on endotheliumdependent vascular reactivity under ischemia/reperfusion conditions.